ANALISIS SISTEM DISTRIBUSI AIR BERSIH MENGGUNAKAN EPANET 2.0 DI PDAM TIRTA LANGKISAU UNIT PELAYANAN LUMPO - Sri Yanti Lisha; Wathri Fitrada; Hendri Sawir; Teguh Pujangga Putra (Sekolah Tinggi Teknologi Industri Padang, 2022)
Lumpo Service Unit is one of the clean water service units in PDAM Tirta Langkisau, Pesisir Selatan Regency, which serves parts of IV Jurai District. The Lumpo Service Unit currently has a production capacity of 3 l/sec or still 24% of the total served population and a fairly high water loss rate (35% or 2,671 m3). This study aims to analyze the clean water needs of the community in the Lumpo Unit area from 2021 and 2025 and analyze the condition of the clean water distribution network system in the Lumpo Service Unit in 2021 and 2025. Analysis of the water distribution system network was carried out using Epanet 2.0. It was found that the water demand in 2021 was 5.45 l/s (22.51 l/s at a service level of 100%) and there was an increase in 2025, namely 28.23 l/s. Analysis of the piping distribution network in 2025 shows that 27 out of a total of 49 junctions have water pressure below the minimum limit for distribution pipe criteria from PERMEN PU No. 18/PRT/M/2007, as well as 13 out of 50 total pipes with water flow rates below the minimum limit of the same criteria of 0.3 m/s.